Optimization of pretreatment and enzymatic hydrolysis of empty fruit bunch for xylose production [electronic resource] - Agnese Jati Anak Charlie, 1985- (2011)
Thesis (Sarjana Kejuruteraan (Bioproses)) - Universiti Teknologi Malaysia, 2011